DEVELOPMENT OF CREATIVE ABILITIES OF FUTURE TEACHERS TECHNOLOGIES - I.V. Dorofeeva (Academy of Cognitive and Natural Sciences, 2008)
In article are considered notions "creative activity", "creative personality", and "creative abilities" and condition to efficiency of the development of the creative abilities of the future teachers technologists.